Perencanaan Pencahayaan Lampu Jalan Dengan Simulasi Dialux Untuk Efisiensi Energi - Lutfi Cahyanto, Iqbal; Ali, Machrus; Nurohmah, Hidayatul (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2025)
Good street lighting planning is essential, especially in areas prone to accidents and crime. Good street lighting can reduce the risk of accidents and increase the sense of security in public areas, providing security, convenience, and comfort for road users, especially at night or in bad weather conditions. However, street lighting is often a significant source of energy consumption. Therefore, optimising the street lighting system to improve energy efficiency is necessary. The study results showed that the existing lighting system using 250 W high-pressure sodium (HPS) lamps has weaknesses in terms of energy efficiency and light distribution quality. Simulations using Dialux showed that the average luminance of existing lighting only reached 0.6 cd/m² with a uniformity level of 0.4, and energy consumption reached 20,000 W along the road. Lighting optimization using 120 W LED lamps provides significant improvements in energy efficiency and lighting quality. The average luminance increased to 0.8 cd/m² with a uniformity of 0.6, while energy consumption decreased by 52%, from 20,000 W to 9,600 W. In addition, the glare level decreased from 30 to 25, indicating an increase in visual comfort. These results indicate that the implementation of LED lights can not only improve the quality of street lighting but also have a positive impact on energy efficiency and reduced operating costs.